High-efficiency energy-saving buildings utilizing potassium tungsten bronze heat-insulating glass and polyethylene glycol/expanded energy storage blanket. (15th September 2022) - Peng, Lihua; Chao, Luomeng; Xu, Ziqing; Yang, Haibin; Zheng, Dapeng; Wei, Boxuan; Sun, Changwei; Cui, Hongzhi
Abstract: The energy shortage crisis is one of the main challenges facing human society. Energy storage blanket (ESB) based on phase change material (PCM) and transparent heat-insulating glass (HIG) based on selective light-absorbing materials show great potential in regulating temperature and reducing building energy consumption. However, the stability of ESB and HIG is insufficient, and there is often a substantial indoor temperature difference when ESB and HIG are applied alone. In this research, stability-enhanced HIG and ESB were prepared. The oxidation and the decline in the heat insulation ability of HIG in air were solved by coating SiO2 film on the surface of Kx WO3 nanoparticles. The low thermal conductivity and the deformation during the phase change process of ESB were solved by encapsulating PCM with expanded graphite. The combined use of HIG and ESB (HIG-ESB) reduces the temperature difference in the test room from 5.9 to 0.5 °C and the maximum indoor temperature from 50.5–56.4 °C to 28.5–28.9 °C. The energy-saving rates of ESB, HIG, and HIG-ESB in different climatic regions of China are evaluated by numerical simulation. The results show that ESB can save energy in all regions, while the HIG increases energy consumption in cold areas and can achieve a stronger energy-saving effect than ESB in mild areas such as Hong Kong and Changsha. Graphical abstract: Image 1 Highlights: The stability of potassium tungsten bronze was improved by coating SiO2 film. The indoor temperature difference of the test room decreased from 5.9 °C to 0.5 °C. The maximum temperature of the test room can be reduced by 49%. An annual energy-saving of 29.7% in Hong Kong was achieved from the simulation.